2007
DOI: 10.1124/mol.107.038083
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin 5-Hydroxytryptamine2C Receptor Signaling in Hypothalamic Proopiomelanocortin Neurons: Role in Energy Homeostasis in Females

Abstract: Hypothalamic proopiomelanocortin (POMC) neurons play a critical role in the regulation of energy balance, and there is a convergence of critical synaptic input including GABA and serotonin on POMC neurons to regulate their output. We found previously that 17␤-estradiol (E 2 ) reduced the potency of the GABA B receptor agonist baclofen to activate G protein-coupled inwardly rectifying potassium (GIRK) channels in hypothalamic POMC neurons through a membrane estrogen receptor (mER) via a G␣ q phospholipase C (PL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(60 citation statements)
references
References 45 publications
3
57
0
Order By: Relevance
“…The positive modulation of CREB activity occurs via ER interactions with metabotropic glutamate receptors 1(mGluR 1) and the negative modulation via mGluR 2/3 ( Figure 1A). The type of interaction, however, is currently unknown, but potentially could be similar to that described for mER and 5HT 2C receptors which have diverse but convergent signaling pathways in arcuate neurons (Qiu et al, 2007). A similar scenario has been hypothesized for the rapid E2-induced activation of μ-opioid receptors in the medial preoptic area associated with female sex behavior (Dewing et al, 2007).…”
Section: Membrane-initiated Signaling Of E2mentioning
confidence: 78%
“…The positive modulation of CREB activity occurs via ER interactions with metabotropic glutamate receptors 1(mGluR 1) and the negative modulation via mGluR 2/3 ( Figure 1A). The type of interaction, however, is currently unknown, but potentially could be similar to that described for mER and 5HT 2C receptors which have diverse but convergent signaling pathways in arcuate neurons (Qiu et al, 2007). A similar scenario has been hypothesized for the rapid E2-induced activation of μ-opioid receptors in the medial preoptic area associated with female sex behavior (Dewing et al, 2007).…”
Section: Membrane-initiated Signaling Of E2mentioning
confidence: 78%
“…In other words, interaction with the HTR2A/2C receptors is associated with a desensitization of the HTR1A receptors, a mechanism that has been proposed to underline the antidepressant efficacy of the serotonergic drugs [Hensler, 2003]. Consistently, Barabanova and coworkers demonstrated that the use of ketanserin (a 5-HT(2A/2C) receptor antagonist) had antidepressant activity in animal models and, of note, c-fos expression was enhanced by this treatment specifically in the in the paraventricular nucleus of hypothalamus [Barabanova et al, 2007;Qiu et al, 2007]. Heisler et al [2007a] recently reported that the chronic activation of the HPA axis, a frequent characteristic of depressive episodes, is dependent on the HTR2C activity, which characterizes the oxitocin and vasopressin producing neurons in the hypothalamic paraventral nucleus as well [Ho et al, 2007].…”
mentioning
confidence: 91%
“…Studies of mutant mice with functional alterations of 5-HT 2C R activity have elucidated some of the mechanisms underlying this important regulation. In the hypothalamus, 5-HT 2C Rs are prominently expressed on POMCcontaining neurons of the ventrolateral arcuate nucleus (Wright et al 1995;Pasqualetti et al 1999;Heisler et al 2002), and serotonin binding to these receptors is thought to contribute to neuronal activation (Qiu et al 2007). POMC neurons in the arcuate are also activated by leptin signaling through the leptin receptor (Cheung et al 1997;Elias et al 1999;Cowley et al 2001) and serotonin signaling through the 5-HT 1B receptor (Ho et al 2007;Nonogaki et al 2007).…”
Section: Dysregulated Organization Of Proopiomelanocortin (Pomc)-medimentioning
confidence: 99%